2008
DOI: 10.1519/jsc.0b013e31816a5c4c
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations on Jump Capacity in Brazilian Volleyball Players Prior to the Under-19 World Championship

Abstract: The under-19 Brazilian volleyball national team has achieved great performances at international competitions. Because the vertical jump capacity is critical for success in volleyball, the purpose of this study was to identify the training-induced adaptations on jump capacity assessed by general and specific tests during 3 different moments (i.e., T1, T2, and T3) of a macrocycle of preparation for the world championship. The sample was composed of 11 athletes from the Brazilian national team-World Champion (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 7 publications
1
40
0
12
Order By: Relevance
“…Stanganelli et al 16 utilizando a mesma abordagem metodológica do presente estudo reportaram valores semelhantes de saltos de ataque e bloqueio para as posições de Centrais e Ponteiros. No presente estudo, foi observado que o número de saltos verticais para execução do ataque no voleibol exerce influência na PSE dos atacantes, com maior impacto para os opostos e pontas apesar das correlações apresentadas serem consideradas de moderada magnitude.…”
Section: Discussionunclassified
“…Stanganelli et al 16 utilizando a mesma abordagem metodológica do presente estudo reportaram valores semelhantes de saltos de ataque e bloqueio para as posições de Centrais e Ponteiros. No presente estudo, foi observado que o número de saltos verticais para execução do ataque no voleibol exerce influência na PSE dos atacantes, com maior impacto para os opostos e pontas apesar das correlações apresentadas serem consideradas de moderada magnitude.…”
Section: Discussionunclassified
“…Consequently, the players' jumping performance was probably poorer due to training reductions during the summer and then, after one season of regular training, the players in both groups experienced normal adaptation to sport. Previous studies have shown that the physical performance, such as jumping performance and throwing velocity, were enhanced during one season of ordinary training or preparation for competition in sports 21,30 and that interruptions in normal training can result in physical capacity reductions 31 . Since jumping is one of the most important tasks in volleyball, it is likely that this ability will improve during one season of volleyball training.…”
Section: Discussionmentioning
confidence: 99%
“…Al analizar el porcentaje de grasa presentado por los atletas de este estudio, encontramos que estos resultados fueron superiores a los obtenidos en atletas juveniles brasileños (8,3 ± 0,9%) (Stanganelli et al, 2008) e italianos (10, 9 ± 1,8%) (Ciccarone et al, 2005), además de los atletas adultos italianos (10,7 ± 1,9%) (Ciccarone et al, 2008) y Iraníes (10,45%) (Koozechian & Nazen, 2002). No obstante, fueron más bajos que los puntajes de los atletas adultos de las selecciones de Venezuela (18,9 ± 3,2%), Uruguay (20,4 ± 2,8%), Paraguay (20,2 ± 2,7%), y Colombia (20,6 ± 0,8%), y de la selección juvenil de Chile (21,6 ± 4,6%) (Flores et al).…”
Section: Posiciónunclassified